DESAIN SUMUR-SUMUR MENGGUNAKAN ELECTRIC SUBMERSIBLE PUMP DALAM MENINGKATKAN PRODUKSI DAN PENGOPTIMALAN WAKTU WORKOVER PADA LAPANGAN X - Budiharto, Trisno
Hydrocarbons in a reservoir flows naturally to the surface at the start of production. Along with oil production, reservoir pressure will drop as a result of the reduction of the volum of the fluid reservoir. This resulted in the production of pressure drop for a given field will go down until it reaches the economic limit a field to production. In this method of artificial lift made necessary to provide energy to the bottom of the well in order to flow naturally again reservoir fluid to the surface to be assessed economically. Electric submersible pump (ESP) is one method of artificial lift made giving energy in the form of kinetic energy is converted to potential energy thereby providing additional pressure. The addition of the pressure was aimed at making the fluid can flow to the wellhead after coming out of the ESP. ESP can provide an increase in the rate of production to the well with the condition who cannot flow or small production rates are judged less economical. In this paper will discuss about the design of ESP on a X field by looking at the condition of the well as production rates go down, the determination of the type of the pump with the rate production criteria at the workover time that the selected ESP can last a long time with the desired production rate. Implementation of a workover installation ESP should be optimized as it pertains to time shut the well and how often the well workover performed. Workover optimisation of ESP can be seen from the design of the pump in restraining the rate of production over the relatively long.